Synthesis of dihydropyrimidinone derivatives using kelubi fruit (Eleiodoxa conferta) as a catalyst and its antibacterial activity - Sari, Ratih Puspita; Nurhadini, Nurhadini; Mahardika, Robby Gus (Asian Journal of Health and Applied Sciences, 2022)
Kelubi fruit is one of the many fruits that grow in Bangka Belitung which has a sour taste. Kelubi fruit contains ascorbic acid, malic acid and oxalic acid. The potency and sour taste of Kelubi fruit can be used as a catalyst in the synthesis of dihydropyrimidinone compounds and activity as antibacterial. Dihydropyrimidinone compounds were synthesized using synthesis with the basic ingredients of benzaldehyde, urea and ethyl acetoacetate using natural catalysts that are more environmentally friendly. The purpose of this study was to determine the optimum volume, time and temperature catalyst used by kelubi fruit to synthesize pyrimidine-derived compounds as antibacterial. The optimization results on the synthesis of dihydropyrimidinone compounds using kelubi fruit water as a catalyst (Eleiodoxa conferta) with a lot of 0.3 mL catalyst, temperature of 50ºC and reaction time of 4 hours with yield of 46.75%. Antibacterial activity of dihydropyrimidinone compounds against Stapylococcus aureus bacteria at a concentration of 10 ppm, 30 ppm including the category and a concentration of 75 ppm including the medium category. Antibacterial activity against Eschericia coli bacteria at concentrations of 30 ppm and 75 ppm was categorized as weak.